METODE DAKWAH DALAM AL-QUR’AN - Faridah Faridah; Siar Ni'mah; Kusnadi Kusnadi (LP2M IAIM Sinjai, 2021)
The Qur'an explains in full how to preach properly and correctly. It is intended that all aspects can run well too. This research is a literature study using the thematic interpretation method, namely setting a da'wah theme as the axis of the study. Therefore, this research makes QS. An-Nahl verse 125 as a focus in tracing the procedures for carrying out da'wah activities. As a conclusion from this study, it was found that there are three types of da'wah methods or methods of da'wah, namely da'wah bi al-hikmah (wisdom), mau'izah hasanah (good advice), and mujadalah bi allatii hiya ahsan (dialogue in a better way)